EFFECT OF POTASSIUM ON GROWTH, YIELD AND QUALITY OF CITRONELLA GRASS - Gusmaini Gusmaini; M. Syakir (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Citronella grass nowadays are developed in the highland that dominated by Andosol soil type. Thus, it is important to find out the proper fertilizer dosage, especially potassium, for citronella grass cultivation in Andosol soil. This study aimed to obtain the optimal of potassium dosage for growth, production and quality of Citronella grass oil. It was conducted at Manoko research station in Lembang, Bandung West Java from July 2014 to August 2015. This research was arranged in randomized block design, with 5 treatments and 5 replication. The treatments consisted of 5 potassium dosages: 1) without potassium, 2) 30 kg/ha K2O, 2) 60 kg/ha K2O, 3) 90 kg/ha K2O, and 5) 120 kg/ha K2O. The application of potassium on Andosol enhanced plant growth, production and oil yield significantly. However, it did not affect the quality of citronella grass oil (citronella and oil content) significantly. The application of 30 kg/ha K2O in citronella grass cultivation on Andosol has the best result. The oil yield was 1.20% (the 1st harvest), 1.28% (The 2nd harvest) and 1.23% (the 3rd harvest), with yield increment 6.9-7.5%. Oil content was 1,40-1,70%. The K nutrient uptake also improved around 11.76%. Citronella content from all treatments ranged from 36.97-37.68%. This result suggested that the low dosage of potassium in Andosol was sufficient to enhance primary metabolites process (indicated by growth and yield). However, it had no direct effect on the secondary metabolite process (represented by essential oil and citronella content). Based on the soil analysis after trial, the K residues in the soil was still high. However, its availability for the plants had to be tested further.Keywords: Cymbopogon nardus, citronella content, oil content, oil yield, potassium.